2016
DOI: 10.14434/josotl.v16i4.20106
|View full text |Cite
|
Sign up to set email alerts
|

You Can Lead Students to Water, but You Can't Make Them Think: An Assessment of Student Engagement and Learning through Student-Centered Teaching

Abstract: The current project conducted an assessment of three student-centered teaching techniques in a criminal justice and criminology research methods class: Team-Based Learning, Incentive-Based Learning, and Flipped Classroom. The project sought to ascertain to what extent these techniques improved or impacted student learning outcomes and engagement in this traditionally difficult course. Results provide empirical evidence that students were significantly engaged with the course and benefited from these pedagogica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Across academic majors, the utilization of student-centered teaching methods is the preferred method for classroom instruction (Barrett et al, 2018;Bradford et al, 2016). Janor et al (2013), in a study of five finance courses taught at a business school in Malaysia, focused on student-centered methods that included case studies, class discussions, group discussions, group projects, and student presentations.…”
Section: Review Of the Literature Teaching Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Across academic majors, the utilization of student-centered teaching methods is the preferred method for classroom instruction (Barrett et al, 2018;Bradford et al, 2016). Janor et al (2013), in a study of five finance courses taught at a business school in Malaysia, focused on student-centered methods that included case studies, class discussions, group discussions, group projects, and student presentations.…”
Section: Review Of the Literature Teaching Methodsmentioning
confidence: 99%
“…Furthermore, student reflections on their impressions of the experiential method and their learning outcomes were positive. In a study of 58 criminal justice majors, Bradford et al (2016) found that student-centered methods like teambased learning, incentive-based learning, and the flipped classroom improved student learning and increased student engagement.…”
Section: Review Of the Literature Teaching Methodsmentioning
confidence: 99%
“…The use of action research, which engages students in the active action inquiry process and improvement of engagement, seems to be lacking. Bradford, Mowder and Bohte (2016) argue that although many instructors may be employing innovative teaching techniques, they are limited by their non-assessment in a research context or the lack of publication regarding the approaches they adopted. It is against this backdrop that this study intends to contribute to the growing body of literature on the improvement of student engagement as well as pave the way for further Pedagogical research is mainly aimed at identifying the best practices that improve learning outcomes of students (Haggis 2009).…”
Section: Introductionmentioning
confidence: 99%
“…As previously mentioned, the learning outcomes that the proposed techniques hope to impact are also worth defining. An increase in students' course grades or improve performance in examinations represent frequently used measures (Haggis 2009); however, other modes include student engagement and other subjective and objective measures of learning (Bradford, Mowder and Bohte 2016). The rationale for the present research was informed by the observation that the average student of Criminology and Criminal Justice disliked the 'Explaining Punishment' (CRI3023-N) module owing to the theoretical and philosophical underpinning often construed as boring; this impacted students performance and engagement.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that active student learning activities, such as those that occur in small groups, improve student performance and engagement as compared with traditional instructional lecture (Bradford, Mowder, & Bohte, 2016;Byun, 2014;Coakley & Sousa, 2013;Freeman et al, 2014;Simonson & Shadle, 2013;Swap & Walter, 2015;J. D. Walker, Cotner, Baepler, & Decker, 2008;L.…”
mentioning
confidence: 99%